Pengaruh Metode Edukasi Flipped Classroom terhadap Peningkatan Pengetahuan Kader Posyandu mengenai Pengukuran Antropometri Balita di Desa Bumiharjo - Ngesti Setyawati; Mohammad Arifin Noor; Indah Sri Wahyuningsih (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Posyandu plays a crucial role in improving community health, particularly in monitoring the growth and development of children during the golden age. However, limitations in the knowledge and skills of Posyandu cadres are still frequently found, especially regarding anthropometric measurement of toddlers. This study aims to examine the effect of the flipped classroom educational method on the knowledge improvement of Posyandu cadres in anthropometric measurement of toddlers in Bumiharjo Village. This research employed a quasi-experimental design with a pretest-posttest control group. A total of 38 respondents were recruited and divided into two groups: the intervention group, which received education using the flipped classroom method, and the control group, which did not receive the same treatment. Data analysis was conducted using the Wilcoxon Signed Rank Test, Mann Whitney U Test, and ANCOVA to control for baseline differences. The results showed a significant improvement in knowledge in the intervention group after treatment (p=0.000), with the proportion of respondents in the “good” knowledge category increasing from 5.3% to 36.8%. In the control group, improvement was observed but limited (p=0.003), with no respondents reaching the “good” category. The Mann Whitney test indicated significant differences in posttest scores between the groups (p=0.000). Furthermore, ANCOVA analysis confirmed that after controlling for pretest scores, posttest scores remained significantly different (F=6.771; p=0.013). In conclusion, the flipped classroom method effectively improves the knowledge of Posyandu cadres regarding toddler anthropometric measurement. This strategy can serve as an innovative and sustainable alternative for cadre training, ultimately enhancing Posyandu service quality in addressing nutritional and health issues among toddlers.